Aspectos entomológicos em povoamentos homogêneos de Acacia mearnsii de Wild - Oliveira, Leonardo da Silva (2007)
The proposed work aimed to investigate the entomological aspects in homogeneous stands of Acacia mearnsii (black wattle). It was considered: insects identification and damage quantification on seeds; treatment effect of seeds and the insecticides application on the aerial part of plants of direct sowing; the survey qualiquantitative by light traps mean; the main species of Coleoptera present in the suppressed trees; the attack characterization of Oncideres impluviata and its influence on wood volume of black wattle. The experiments were carried out in cultivated areas of black wattle situated at the municipality of Butiá and Minas do Leão in the carboniferous region of Rio Grande do Sul during March 2004 to July 2006. It was verified that the Stator limbatus (Coleoptera: Chrysomelidae) caused expressive damage to the black wattle seeds. There was no statistical increase in relation to the use of insecticides to the directly sowing, however black wattle plants submitted to thiamethoxam application on the aerial part showed better development. Among the 11 orders collected by light traps the populations of lepidoptera, coleoptera and hemiptera were quantitatively pointed. Sigara sp. (Hemiptera: Corixidae), Conoderus alfredense (Coleoptera: Elateridae) and Plectris crassa (Coleoptera: Scarabaeidae) were the species more frequents, abundant and constants collected by the light traps. At the qualitative survey made in suppressed trees it was observed 40 species of Coleoptera distributed in ten families, focusing in Curculionidae with twelve representatives, Cerambycidae with ten and Scarabaeidae with nine species. It was verified that O. impluviata attacks the high parts of the tree, independent of age, from the borders into the stand and cuts the branches averaging 14mm of diameter and 1.4 m of length. These branches present high contents of nitrogen and phosphorus in their chemical composition when compared to non-cut branches. The attack of O. impluviata did not reduce the wood volume produced for black wattle trees.